2020
DOI: 10.1038/s41598-020-60754-4
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of 1-Deoxy-, 3-Deoxy- and N-Methyl-Ceramides in Skin Barrier Lipid Models

Abstract: Ceramides (Cer) are essential components of the skin permeability barrier. To probe the role of Cer polar head groups involved in the interfacial hydrogen bonding, the N-lignoceroyl sphingosine polar head was modified by removing the hydroxyls in C-1 (1-deoxy-Cer) or C-3 positions (3-deoxy-Cer) and by Nmethylation of amide group (N-Me-Cer). Multilamellar skin lipid models were prepared as equimolar mixtures of Cer, lignoceric acid and cholesterol, with 5 wt% cholesteryl sulfate. In the 1-deoxy-Cerbased models,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…If a specific Raman spectrum can be used as an indicator to diagnose skin inflammation, it would be desirable to target substances that are present in the skin at higher concentrations 21 or that have extremely distinctive and sharp spectra, such as lipids or phospholipids. 24 Although we could not identify inflammation-specific substances such as cytokines, we did observe several inflammation-induced changes in the Raman spectra. The newlyemerged spectra in the 1500-1650 cm −1 region were consistent with the Raman spectrum of haem protein, 25 which we considered to represent vasodilation due to skin inflammation.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…If a specific Raman spectrum can be used as an indicator to diagnose skin inflammation, it would be desirable to target substances that are present in the skin at higher concentrations 21 or that have extremely distinctive and sharp spectra, such as lipids or phospholipids. 24 Although we could not identify inflammation-specific substances such as cytokines, we did observe several inflammation-induced changes in the Raman spectra. The newlyemerged spectra in the 1500-1650 cm −1 region were consistent with the Raman spectrum of haem protein, 25 which we considered to represent vasodilation due to skin inflammation.…”
Section: Discussionmentioning
confidence: 73%
“…If a specific Raman spectrum can be used as an indicator to diagnose skin inflammation, it would be desirable to target substances that are present in the skin at higher concentrations 21 or that have extremely distinctive and sharp spectra, such as lipids or phospholipids. 24…”
Section: Discussionmentioning
confidence: 99%
“…Our studies have revealed that these atypical lipids, even in very small concentrations, significantly affect the intramolecular interactions of membrane lipids and impair membrane fluidity [49,50]. Future studies should investigate whether the change of the membrane properties by these lipids may contribute to their pathobiological role [60].…”
Section: Atypical Sphingoid Bases For Exploring Biophysical Properties Of Non-canonical Sphingolipidsmentioning
confidence: 78%
“…Aer carefully removing the water with a pipette, the uorescence spectrum was obtained with excitation at 405 nm and emission at 450-700 nm. We added 1.0 M HCl and 0.1 M NaOH to the 50 mM FDD to adjust the pH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The uorescence intensity of FDD at different H was then measured using a uorescence spectrophotometer (l ex ¼ 405 nm).…”
Section: General Procedures For Uorescence Measurementmentioning
confidence: 99%
“…1,2 As an important structural component of the skin barrier, lipids have an irreplaceable function in the maintenance of the permeability barrier function of the skin and they also play an antimicrobial role in the skin's immune defence system. 3,4 Cholesterol is one of the major skin barrier lipids; about 30% of the cholesterol in the human body is synthesized in the skin, and 10% to 15% of cholesterol is metabolized through the skin. 5 A study has reported that the physiological level of cholesterol in the stratum corneum (SC) appears to exceed its miscibility with other barrier lipids, and a 0.4 : 1 : 1 M ratio of Chol/ceramides/fatty acids appears sufficient for skin lipids to limit water loss and prevent the entry of environmental substances; the stratum corneum cholesterol may have roles in the skin other than barrier function.…”
Section: Introductionmentioning
confidence: 99%